ANALISIS KEUNTUNGAN USAHA TEMPE SEDAP â€œANDIKAâ€ DI KELURAHAN BAHU KECAMATAN MALALAYANG KOTA MANADO - Olivia Claudia Pantas; Lyndon Reindhard Jacob Pangemanan; Rine ., Kaunang (AGRI-SOSIOEKONOMI, 2021)
The purpose of this study was to analyze the profits received by Tempe Sedap â€œANDHIKAâ€ home industry business in the village of Bahu, Malalayang Sub-District in one production process. This research was conducted for 3 months from October to December 2020. The research method used in this research is a case study. The data taken in this research is primary data using direct interview techniques with business owners using a list of questions that have been prepared in advance. The data collected in this study were then analyzed using profit analysis by calculating the difference between revenue and the costs used and then continued with the Revenue Cost Ratio (R / C) Analysis formula. Based on the research results, it can be concluded that the Tempe Sedap "ANDHIKA" business in the Village of Bahu , Malalayang Sub-District, Manado City is very profitable and gets a value of R / C = 1.35 which means this industry is profitable and feasible to be developed.